A necessidade de interveniência sindical na dispensa coletiva - Fé, Priscila Mousinho De Moura (2018)
The object of the present research consists in the collective dismissal of workers and the limits to their valid and legitimate configuration within the scope of the dismissal employment power. It is not a question of the negative, but of the possibility of existence of the institute, once observed the beacons established by the current legal order, among which stands out the one that imposes collective bargaining. It is investigated to what extent the collective exemption of employee’s demands for their regular and lithy exercise the submission to union intervention, even after the advent of Law 13467/17. Initially, it examines the individual labor contract as to its origin in order to eliminate it, establishing the distinctions between collective dismissal and individual workers. Next, we analyze the legal omission about the concept, characteristics, requirements and procediment of collective dispensations, examining the doctrinal and normative constructions, internal and international in relation to them. The legal position established prior to the Labor Reform promoted in 2017 is then systematized. Afterwards, the grounds that led to the publication of Law 13467/2017 and provisional norm by the head of the Executive Branch ("Medida Provisória 808/2017"), without forgetting the jurisprudential and summative understandings after -Reform and non-binding interpretive guidance created to guide the work of the labor law operators. Ultimately, the legal nature of the collective right of collective dispensation is examined in the light of the legal framework available to provide for the obligation of trade union intervention. It is concluded that it is indispensable to prior labor union participation in collective dispensation, in spite of the provisions of Article 477-A of the CLT, due to the recognition of the normativity of the principles and of conforming reading, which can be seen through the mere exercise of interpretation of the Basic Law, to raise The Law to the law.